Knowledge, Attitudes, and HIV/AIDS Risk Behaviors of Myanmar Migrant Workers in Thailand - Rakkapao, Nitchamon; Kiattisaksiri, Pradabduang; Samakkekarom, Ronnapoom (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: HIV/AIDS is s ll a problem in the health care system of developing countries. Migrant workers are considered a vulnerable popula on for HIV infec on. The current informa on on HIV/AIDS and migrant workers is useful to provide suitable effec ve health interven ons for the preven on of HIV/AIDS. This study aims to describe knowledge, a tudes and HIV/AIDS risk behaviors among Myanmar male migrant workers in Thailand. Methods: A cross-sec onal study was conducted in Myanmar male migrant workers aged 18-60 years collected from February to May 2018. A total of 400 migrant workers who live in Patumthani provinces were selected by a convenience sampling method. Descrip ve sta s cs were used to explore knowledge, a tudes and HIV/AIDS risk behaviors of par cipants. Results: The mean age of the par cipants was 33 years, ages ranged from 18 to 60 years old, achieved pri- mary school (40.40%), and married (54.30%). An average living in Thailand was 3.25 years and monthly income was 9,166 baht (?286 USD), respec vely. A majority of par cipants had a poor level of HIV/AIDS knowledge (55.25%) and a fair level of an a tude about HIV/AIDS disease and preven on (61.25%). Risk behaviors related to HIV/AIDS of par cipants who had sex with non-partners were 40.58%. Conclusion: Most par cipants had poor knowledge and a fair a tude of HIV/AIDS. Risk behaviors related to HIV/AIDS of the par cipants were rela vely high. Moreover, most of par cipants had less access to health care services. This results confirmed that an urgent need to provide health interven on to increase knowledge on HIV/AIDS of Myanmar migrant workers in Thailand.